Design of voltage stabilization circuit for wind power generation – part I (Simulation) - Abas, M. F.; Mohibullah; Mariun, N.; Bashi, S. M. (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.